Introduction to MSME Products in Sidoarjo Regency Using Augmented Reality - Nur Huda; Sumarno (Universitas Muhammadiyah Sidoarjo, 2021)
Explanation of UMKMs (Micro, Small, and Medium Enterprises) is a business that has a very important role in the economy of a country, both in terms of the existing in the field of employment or created in terms of the number of businesses that exist. Explanation of UMKMs in terms of micro enterprises can also be interpreted as businesses owned by individuals or a productive economic business entity in accordance with the criteria of various micro, small, and medium enterprises. The purpose of this research is so that students can design an application that is able to display 3D objects of UMKM products, and also to introduce UMKM products to consumers more easily and more efficiently. The method used is marked based tracking, then used as a marker is a card with a picture of UMKM products, and also augmented reality is using vuforia library as a database of UMKM product identifiers displayed, and unity engine software using the C# programming language. The result of the research obtained is an augmented reality application that can bring up UMKM products in the form of a virtual 3-dimensional object display. The benefit of this research is that the augmented reality application of UMKM products can make it easier for manufacturers to introduce their products to consumers.